2016
DOI: 10.1111/iej.12669
|View full text |Cite
|
Sign up to set email alerts
|

Attachment and proliferation of dental pulp stem cells on dentine treated with different regenerative endodontic protocols

Abstract: Introduction To investigate the attachment and proliferation of dental pulp stem cells (DPSC)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 37 publications
0
44
1
1
Order By: Relevance
“…This antibiofilm effect was exactly similar to 20 mg mL −1 clindamycin, so that the same concentration of clindamycin alone was showed the same efficacy in comparison with TAP. The common used concentration of TAP in the clinical condition is 1000 mg mL −1 that recently has been shown toxic for apical papillae and dental pulp stem cells . Recent studies indicated highly unfavorable effect of TAP on surface roughness and the colour of dentine , so a reduced concentration of TAP in our study was used.…”
Section: Discussionmentioning
confidence: 99%
“…This antibiofilm effect was exactly similar to 20 mg mL −1 clindamycin, so that the same concentration of clindamycin alone was showed the same efficacy in comparison with TAP. The common used concentration of TAP in the clinical condition is 1000 mg mL −1 that recently has been shown toxic for apical papillae and dental pulp stem cells . Recent studies indicated highly unfavorable effect of TAP on surface roughness and the colour of dentine , so a reduced concentration of TAP in our study was used.…”
Section: Discussionmentioning
confidence: 99%
“…Even at low concentrations, TAP has unwanted effects on the proliferative capacity and mineralized matrix formation of dental pulp cells and apical papilla cells [ 50 ]. According to several studies, a concentration of 0.125 mg/mL of TAP has no cytotoxic effect on the stem cells; thus, it is expected that a concentration of the antibiotic combination with the lowest possible side effects and adequate ability for removing microorganisms, particularly Enterococcus faecalis ( E. faecalis ) must be used during endodontic treatments [ 50 51 ]. The proper and careful combination of the 3 antibiotics has shown to create an appropriate environment for the cell attachment to occur, and to have enough dislocation resistance [ 52 ] for mineral trioxide aggregate (MTA) or calcium enriched mixture (CEM) cement as the bio-regenerative dressing.…”
Section: Reviewmentioning
confidence: 99%
“…Indeed, using current techniques, it appears that revitalization will at best stimulate repair, not regeneration with minimal gain in root length over traditional apexification techniques [7, 35]. As a result, specific attention was directed to developing methods, which harness the fossilized bioactive dentin matrix components, including GFs and other signaling molecules, with irrigants, medicaments, and materials [4043]. Additionally, new functionalized scaffolds are being investigated as a mechanism for controlled delivery of angiogenic and other exogenous GFs to support and improve the regenerative response [31, 44].…”
Section: Reviewmentioning
confidence: 99%